2012
DOI: 10.1128/aac.00264-12
|View full text |Cite
|
Sign up to set email alerts
|

Inducible and Constitutive Activation of Two Polymorphic Promoter Alleles of the Candida albicans Multidrug Efflux Pump MDR1

Abstract: Overexpression of the multidrug efflux pump MDR1 confers resistance to the antifungal drug fluconazole on Candida albicans. It has been reported that two types of MDR1 promoters exist in C. albicans and that homozygosity for the allele with higher activity may promote fluconazole resistance. We found that the two MDR1 promoter alleles in strain SC5314 were equally well activated by inducing chemicals or hyperactive forms of the transcription factors Mrr1 and Cap1, which control MDR1 expression. In addition, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, it has been reported that Spt-Ada-Gcn5-acetyltransferase complex subunit Ada2 promotes Cap1-mediated upregulation of the multidrug efflux pump MDR1 in fluconazole-resistant C. albicans ( 11 ). Additionally, a study by Sasse et al ( 12 ) demonstrated that two polymorphic promoter alleles in MDR1 may be associated with the development of fluconazole resistance. A study by Wang et al ( 13 ) identified mutations in the EGR11 gene in azole-resistant C. albicans .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that Spt-Ada-Gcn5-acetyltransferase complex subunit Ada2 promotes Cap1-mediated upregulation of the multidrug efflux pump MDR1 in fluconazole-resistant C. albicans ( 11 ). Additionally, a study by Sasse et al ( 12 ) demonstrated that two polymorphic promoter alleles in MDR1 may be associated with the development of fluconazole resistance. A study by Wang et al ( 13 ) identified mutations in the EGR11 gene in azole-resistant C. albicans .…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms that contribute to fluconazole resistance in C. albicans have been elucidated, including increased drug efflux and mutations or overexpression of the ERG11 gene, which encodes lanosterol 14␣-demethylase [4][5][6]. Point mutations in ERG11 contribute to decreased binding affinity of azoles for their target enzyme Erg11p and increased azole resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Cap1 is a transcriptional regulator. In C. albicans, it promotes expression of the major facilitator superfamily (MFS) drug transporter MDR1, and it has been reported that C-terminal truncations of CAP1, like those we isolated from our drug-resistance screen, cause a hyperactive phenotype which increases MDR1 expression and thereby increases fluconazole resistance (61)(62)(63)(64). To test whether this is also the case with our resistant C. auris CAP1 mutants, we used RT-qPCR to examine the levels of MDR1 expression along with two other drug transporters: CDR1 and CDR2.…”
Section: Cap1 Truncation Results In Increased Mdr1 Expressionmentioning
confidence: 91%